Paleobiology of Pleistocene large land mammals from the Brazilian Pampa - Carrasco, Thayara Silveira [UNESP]; Ribeiro, Ana Maria; da Mota, Gabriel Santos; Buchmann, Francisco Sekiguchi [UNESP] (Elsevier, 2023)
The southern Brazilian Pleistocene fauna exhibited a rich diversity of large mammalian herbivores, which are now extinct or locally extinct. In this study, we employed stable isotope analysis to investigate the past ecology of these animals. Specifically, we examined the carbonate fraction of bones and teeth and utilized compiled carbon and oxygen isotopic ratios from previous research publications. The δ13C values indicated that most specimens inhabited grassland environments, which aligns with environmental reconstructions based on pollen records of the “Campos” region. The dominant food resource for these herbivores consisted of C3 photosynthesizers, mainly cool-season grasses. This preference can be attributed to the higher abundance and nutritional quality of cool-season grasses compared with warm-season grasses employing C4 photosynthesis. The variability in δ18O values within and between taxa may suggest a seasonal climate. Based on these findings, we conclude that the environmental changes during the Pleistocene-Holocene transition were detrimental to the survival of these large herbivores.
Keywords: Diet; Habitat; Megafauna; Quaternary; South America; Stable isotopes